2021
DOI: 10.14309/01.ajg.0000798752.72296.f3
|View full text |Cite
|
Sign up to set email alerts
|

P038 Ozanimod First-Dose Cardiac Effects in Patients with Moderately to Severely Active Ulcerative Colitis and Relapsing Multiple Sclerosis

Abstract: BACKGROUND: Ozanimod, an oral sphingosine 1-phosphate (S1P) receptor modulator that selectively targets S1P1 and S1P5, is approved in the US for treating moderately to severely active ulcerative colitis (UC) and in multiple countries for treating relapsing forms of multiple sclerosis (MS). In a Phase 1 study of ozanimod in healthy participants, first-dose cardiac effects were mitigated with gradual dose escalation. Based on these results, an initial 7-day ozanimod dose escalation regimen was implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, no cases of second‐ or third‐degree AV block were observed 113 . In phase 2 and phase 3 RCTs of ozanimod in UC, following the first dose, the mean decrease in heart rate was marginal (0.7 beats per minute from baseline) within the first 5 h, and returned to baseline after 6 h 114 …”
Section: Risk Of Cardiac Conduction Abnormalities With Smdsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, no cases of second‐ or third‐degree AV block were observed 113 . In phase 2 and phase 3 RCTs of ozanimod in UC, following the first dose, the mean decrease in heart rate was marginal (0.7 beats per minute from baseline) within the first 5 h, and returned to baseline after 6 h 114 …”
Section: Risk Of Cardiac Conduction Abnormalities With Smdsmentioning
confidence: 97%
“…In addition, no cases of second-or third-degree AV block were observed. 113 In phase 2 and phase 3 RCTs of ozanimod in UC, following the first dose, the mean decrease in heart rate was marginal (0.7 beats per minute from baseline) within the first 5 h, and returned to baseline after 6 h. 114 Pooled data across phase 3 RCTs in patients with UC and multiple sclerosis indicate that the risk of bradycardia with ozanimod was low and primarily occurs in the induction period. Additionally, the use of ozanimod for longer periods was not associated with an increased risk of MACE.…”
Section: Evidence From Ibd Clinical Trialsmentioning
confidence: 99%
“…Post hoc analyses of phases 2 and 3 clinical trial data confirmed that the ozanimod dose titration schema mitigates first-dose cardiac effects in patients with UC and MS; transient and minimal reductions in heart rate occurred with the first dose of ozanimod, and there were few [<1%] first-dose, cardiac AEs with ozanimod in patients with or without a history of cardiac disorders. 46 Additional post hoc analyses of phase 3 clinical trial data demonstrated a low incidence of cardiac AEs [≤2.2%] and no increased risk of thromboembolic events or major adverse cardiac events [eg, cardiovascular death, myocardial infarction, stroke] with up to 1 year of ozanimod treatment in patients with UC; discontinuations due to cardiac AEs were low [<1%] and there were no cardiovascular-related deaths. 47 , 48 A similar incidence of cardiac AEs [2.8%] was reported in patients with MS with up to 5 years of ozanimod treatment in an OLE that enrolled patients from phase 1–3 trials.…”
Section: Guide To Using Ozanimod For the Treatment Of Ucmentioning
confidence: 99%